Variability in Markingnut (Semecarpus anacardium L.) Accessions from Marathwada Region of Maharashtra State - N A Deshmukh (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2010)
A survey was conducted in markingnut growing area (Aurangabad, Beed, Hingoli, Nanded and Parbhani districts) of Marathwada region in Maharashtra (India) during 2005-07 to assess existing natural variability for superior genotypes and good fruit-quality among 264 markingnut seedling trees and 27 superior clones. All the genotypes showed considerable variability with respect to physico-chemical characters. Fruit weight varied from 5.0 (PD-2) to 15.88 g (HD-5) and hypocarp weight from 3.37 (AD-2 and PD-1) to 10.67g (HD-5). Individual pericarp weight ranged from 1.59 (PD-2) to 5.21 g (HD-5) and kernel weight ranged from 0.16 (PD-2) to 1.07 g (HD-5). There was wide variation in chemical characteristics. Also, T.S.S. varied from 5.67 (BD-3) to 13.10°B (ND-3) and titratable acidity from 0.22 (AD-1) to 1.93% (BD-3). Kernel protein content ranged from 13.22 (AD-2) to 25.75% (HD-5), carbohydrate content from 17.92 (PD-3) to 26.91% (AD-3), fat content from 31.57 (HD-3) to 40.59% (PD-4) and pericarp oil (B.S.L) content from 27.80 (BD-4) to 41.74% (HD-2). On the basis of physico-chemical characters assessed, genotypes HD-5 and ND-3 were found to be most promising.